Zhen-Wu-Tang Induced Mitophagy to Protect Mitochondrial Function in Chronic Glomerulonephritis via PI3K/AKT/mTOR and AMPK Pathways - Liu, Bihao; Cao, Yiwen; Wang, Dejuan; Zhou, Yuan; Zhang, Peichun; Wu, Junbiao; Chen, Junqi; Qiu, Jianguang; Zhou, Jiuyao (Frontiers in Pharmacology, 2021)
Chronic glomerulonephritis (CGN) is the one of the major causes of the end-stage kidney disease. Zhen-wu-tang (ZWT), as a famous Chinese herbal prescription, is widely used in China for CGN therapy in clinic. However, the mechanism of ZWT in CGN has not been fully understood. The present study explored the therapeutic effect and the underlying mechanism of ZWT on mitochondrial function in cationic bovine serum albumin (C-BSA)-induced CGN model rats and tumor necrosis factor (TNF-α) damaged mouse podocytes. The renal functions were measured by serum creatinine (Scr) and blood urea nitrogen (BUN), renal pathological changes and ultrastructure of kidney tissue were evaluated by periodic acid schiff (PAS)-staining and transmission electron microscopy. The levels of antioxidases including mitochondrial catalase (CAT), superoxide dismutase 2 (SOD2) and peroxiredoxin 3 (PRDX3) in CGN rats were examined by real time-PCR. The mitochondrial functions of podocytes were measured by ATP concentration, mitochondrial membrane potential (MMP) and mitochondrial ROS (mtROS). For mitophagy level detection, the expressions of mitophagy related proteins including LC3, p62, heat shock protein 60 (HSP60), translocase of outer mitochondrial membrane 20 (TOMM20) were measured by Western blot, as the co-location of LC3 and mitochondrial marker COX IV were evaluated by immunofluorescence. Our results manifested that ZWT ameliorated CGN model rats by a remarkable decreased of Scr and BUN, inhibition of mesangial matrix proliferation, protect against foot processes fusion and basement-membrane thickening. More importantly, ZWT protect against mitochondrial dysfunction by increasing the expressions of CAT, SOD2 and PRDX3 in CGN model rats, as well as increased ATP content and MMP in podocytes, decreased excessive mtROS. Furthermore, ZWT induced mitophagy in CGN through increasing the expression of LC3, and decreasing p62, HSP60 and TOMM20, ZWT also enhanced the co-location of LC3 to mitochondria. We found that ZWT inhibited PI3K/AKT/mTOR pathway, which could be disturbed by PI3K inhibitor LY294002 and agonist insulin-like growth factor 1. Moreover, ZWT reversed the inhibition of AMPK pathway in CGN. Overall, ZWT ameliorated renal mitochondrial dysfunction probably by inducing mitophagy via PI3K/AKT/mTOR and AMPK pathway.